If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 + -3 = 2x + 6 Reorder the terms: -3 + -3 + 2x = 2x + 6 Combine like terms: -3 + -3 = -6 -6 + 2x = 2x + 6 Reorder the terms: -6 + 2x = 6 + 2x Add '-2x' to each side of the equation. -6 + 2x + -2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 0 = 6 + 2x + -2x -6 = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 = 6 + 0 -6 = 6 Solving -6 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2(x-1)=-x+7 | | -80=2/3x-6x | | 3/7x5/7x1/2 | | .0132xy-0.4183x+0.1896y=0 | | -48/60 | | (5X-6)=3X+4 | | ln(x^2-x)=ln(30) | | 2x^3+11x^2+17x+6=0 | | 174=2(4y)+2(3y+3) | | 24x^2+99x+12= | | 4x-4y+7-1= | | -15x+31p=62 | | 174=2(4x)+2(5x-3) | | 6x-2/3x=80 | | 20t(t+3)=19t-20 | | x/.1=900 | | 80=4x+x+3+5x-3 | | x*.1=900 | | (4x)1/2(2x4/3) | | x-.1=900 | | 129+32x=90+45x | | =(-5)+8 | | 3x+8y+9x= | | 180=75+x+x | | 66=2(2z)+2(11)+2(12)+2(3z-1)+2(z+2) | | 7(x+8)=8+7x+15 | | .5x-1.5+1.5-x=-5x | | .25(3x+1)-.625x=.5x | | 8(2b+7)=4(b+10) | | =1-7 | | 2(x-3)+2(3x-3)=2x+2(2x-1) | | 3(6-z)+6z= |